(untitled) (Journal of the College of Basic Education, 2022)
The world of poetry is the world of fertile imagination that breaks the collar of reality to spark salesexpressive and creative spaces; breaks space and time; And launch into the world of creativity artistic imagescolored with the feather of inspiration; So you look at reality from angles far from the tangible and the tangible. angles crossAbout the poet’s ability to find new pictorial charges that link the vocabulary knot in a visual atmosphereNew, the image is an important pillar of the artistic construction of the poem; And an important methodexpression; It is the mirror through which the poet tries to portray everything that waves his inner worldColorful and different feelings and sensations float on the body of the poetic text throughlanguage formations; that provide us with vivid and vibrant images; So that it seems to the reader of the poem as ifHe does not know ((Is he reading the written poem or witnessing a scene from the scenes of existence))!